Decision support for water management for integrating aquaculture in small-scale irrigation systems: a case for the Chingale catchment in Malawi. Project Brief - Kam, Suan Pheng; Cai X; Sood, A.; Hoanh, Chu Thai; Yen, B.T.; Nagoli J; Chijere A (WorldFish, 2013)
A three-year project was funded by the BMZ/GIZ to examine the benefits of integrating aquaculture and small scale irrigation by identifying improved water allocation and management strategies under current and future climate change scenarios. An integrated modeling approach was adopted to analyze the complex issues involved in the decision processes. A water budgeting approach was used in estimating and balancing the water resources available to farming communities (the supply aspect) and the water demand for agricultural use, including crops and fish farming, within a catchment. Adjustments in water allocation and management across and within sub-catchments may then be explored at and beyond the farm level to achieve improved productivity from the integrated farming system while maintaining sustainability and equity in development.